Implementation of The Distribution of Inheritance of Afwezig People In Bantul Regency, Yogyakarta Special Region - Endang Heriyani; Prihati Yuniarlin (Journal Research of Social Science, Economics, and Management, 2022)
The person who is afwezig cannot be known with certainty whether he is alive or deceased. An afwezig person is a person who leaves his place of residence. In practice the right of heirs to demand the division of inherited property faces obstacles because the person who leaves the property in a state of afwezig. This research is normative and empirical legal research. This study aims to find out how the concept of the division of inheritance property belongs to afwezig people according to the Civil Code, and how is the implementation of the division of inheritance property belonging to afwezig people in Bantul Regency, DIY?. From the results of the study, it is known: (1) The concept of division of inheritance property belonging to afwezig is regulated in Articles 463 to 484 of the Penal Code, which specifies that the heirs are entitled to take the inheritance of the afwezig, after a judge's ruling that the afwezig 'may have died', with the obligation to make a record of the property taken, and must carry out calculations, accountability and hand over to the afwezig, if the afwezig returns to his place of residence, (2) The implementation of the division of the estate of the afwezig in Bantul District can only be carried out after there is an afwezig determination from the District Court. So the circumstances of a person's afwezig must be proved by the existence of an injunction from the District Court. In practice it turns out that the afwezig returns back to his place of residence, after his property is bequeathed by his brother. Furthermore, the property of the person who was afwezig by his brother was returned, but only part of it, so it did not follow the provisions of Article 482 of the Civil Code.